PENGEMBANGAN SISTEM ASESMEN HASIL BELAJAR SISWA SEKOLAH MENENGAH ATAS DALAM PENJASORKES MATERI PERMAINAN BOLAVOLI - Guntur, - (Jurnal Pendidikan Jasmani Indonesia, 2015)
The purpose of this research is to develop a system of assessment of student learning outcomes in sports educationsubjects, the volleyball game that valid and reliable. This type of research is the development of research. Theresearch model is the model of development chosen educational research and development developed by Borgand Gall, with the procedure: through four phases: a preliminary study, the development stage, trial phase, anddissemination phases. Subjects of this study consisted of two elements, namely educators and high school studentsin the five districts in the province including SMAN 1 Yogyakarta, Wates SMAN 2, SMAN 1 Seyegan, SMAN 1 Sewon,SMAN 1 Tanjung Sari. Determination of the coefficient of reliability assessment instruments performed using theprogram package genova by Cric and L.Brennan the variance component is person, rater, item, person and raterinteractions, and errors, as well as the interrater Cohen’s Kappa coefficient. Conclusion The results of this studyare: (1) learning outcomes assessment instruments of sports education is observation sheet (check list) and rubric,(2) Characteristics of learning outcomes assessment instruments in sports education high school volleyball game inparticular materials that include validity, reliability, tested, (3) competence profile volleyball game practice results insports education subjects in High School showed that, 93 % or as many as 112 students were declared competent.It is declared that incompetent by 7 % or as many as eight students.Keywords: Development, Assessment, Learning Outcomes, Sports Education and Health, Volleyball.